Overcoming Cyberbully : A Web Based System (Mobile Friendly) - Anandan, Muginesh Kumar (IRC, 2020)
Overcoming cyberbully, a web based system(mobile friendly) idea is proposed which mainly aimed for cyberbully victims to share their stories and get guides from experts to overcome their situation. This idea was proposed mainly because of censorious situation which is increase in number of cyberbully victims in Malaysia and globally. Due to cyberbully, there are many suicidal cases and depression where the victims does not have a platform to share their stories in order to get help to cope with cyberbully from the experts such as counsellor and psychiatrist. Therefore, this report provides an overall idea and development of Overcoming Cyberbully : A Web Based System(Mobile Friendly). Furthermore, past literature was gathered in order to come up with this web based idea with waterfall methodology was used as the system development basis. Going through the current cyberbully issues which mainly cause the development of this web based system idea to help cyberbully victims on coping strategies. By the end of this project development, the aim needed to be fulfilled which is cyberbully victims are assisted.